Determinan Nilai Perusahaan Dengan Dimoderasi Tingkat Financial Distress Pada Perusahaan Telekomunikasi - Nasution, Lily Karlina; Murni, Mayang (UNIVERSITAS DHARMAWANGSA, 2025)
The telecommunications industry is a strategic sector in supporting information and communication infrastructure in the digital era, which faces challenges in the form of intense competition, large investment needs, and demands for continuous innovation. This study aims to analyze the effect of firm size and capital structure on firm value, as well as the role of the level of financial distress as a moderating variable in telecommunications companies listed on the Indonesia Stock Exchange (IDX) for the period 2014-2023. This study uses a descriptive quantitative approach with secondary data analyzed through multiple linear regression and Moderated Regression Analysis (MRA). The results showed that partially, company size has a positive and significant effect on firm value, while capital structure has no significant effect. Simultaneously, firm size and capital structure have a significant effect on firm value. However, the level of financial distress is not able to moderate the effect of firm size and capital structure on firm value